Kemasaman Tanah dan Sebaran Senyawa Pirit pada Berbagai Kedalaman Tanah Pasang Surut - Muhammad Zakir Maulidi; Zuraida Titin Mariana; Bambang Joko Priatmadi (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Soil acidity (pH) is the main obstacle in tidal swampland. The high soil acidity (pH < 4.0) causes an increase in the solubility of iron (Fe). The high soil acidity affects the balance of chemical reactions in the soil and the availability of nutrients in the soil. The purpose of this study was to determine soil acidity (pH), redox potential (Eh), and soluble Fe at at varying soil depths with different pyrite locations in tidal swampland. This study used a nested design and studied the following factors: 1) Depth of pyrite 0-50 cm layer (actual acid sulfate soil) and 50-100 cm layer (potential acid sulfate soil). 2) Soil depth includes 0-25 cm, 25-50 cm, 50-75 cm, and 75-100 cm. Soil samples were taken at the depth where pyrite was detected, with 3 replicates at each soil depth. This resulted in a total of 24 experimental units. The depth of the nested soil coincided with the depth of the pyrite. The study analyzed the acidity of acid sulphate soil, redox potential, and dissolved Fe at pyrite locations within soil depths of 0-100 cm and 0-25 cm, 25-50 cm, 50-75 cm, and 75-100 cm. The results indicate that there was no significant difference in the measurements between the various soil depths of 0-50 cm and 50-100 cm.